Answer this by expanding the brackets 20 POINTS!
![Answer this by expanding the brackets 20 POINTS class=](https://us-static.z-dn.net/files/d35/acd36ae5b28ea5d27f7ca2aac46b7f80.jpg)
Answer:
Below
Step-by-step explanation:
(y - 9)(y - 7) = [tex]y^2-16y+63[/tex]
(2y + 2)(y + 1) = [tex]2y^2+4y+2[/tex]
(2y + 6)(y + 3) = [tex]2y^2+12y+18[/tex]
(3y + 4)(y + 5) = [tex]3y^2+19y+20[/tex]
(2y - 7)(y + 2) = [tex]2y^2-3y-14[/tex]
Answer:
[tex]\huge \boxed{y^2 - 16y + 63}[/tex]
[tex]\rule[225]{225}{2}[/tex]
Step-by-step explanation:
Solving for the first problem:
(y-9)(y-7)
y(y-7)-9(y-7)
y² - 7y - 9y + 63
y² - 16y + 63
[tex]\rule[225]{225}{2}[/tex]